Management of oral cavity disorders during chemotherapy in oncologic patients - Nanobashvili, Ketevan (Caucasus Journal of Health Sciences and Public Health, 2018)
Chemotherapy is an important part of modern methods for treatment of oncologic diseases. As any medication or method, the chemotherapeutical agents also have complications and side effects, from which our interest is the changes in oral cavity during and after of cancer treatment. By using of chemotherapeutic agents, the majority of patients may develop the complications of the oral health. The literature describes mucosits, oral pain, infection, hemorrhages, xerotomy, neurological and nutritional problems. Each of them is a potential threat to the patient's general condition, according to chronological or dental age - for oral hard or soft tissues. These factors will cause significant violations in future permanent dentition, also problems – such dysphagia, dysphonia, development of oral organs and face. Unfortunately, in literature there is less information about the condition of pediatric patients, which are subject of chemotherapy for oncologic diagnosis. Accordingly, there is less information about maintaining the conditions for facilitating prevention of dangerous changes and for the development of future permanent dentition. The goal of the research is to find information about frequency and quality of the damage in oral cavity caused by chemotherapy in oncologic pediatric patients. Also, to develop the special methodology regarding to avoid and prevent vulnerability of the child’s health condition because of pathological changes in oral cavity.